Using economic evidence to support policy decisions to fund interventions for non-communicable diseases. (20th May 2019) - Bertram, Melanie; Banatvala, Nick; Kulikov, Alexey; Belausteguigoitia, Itziar; Sandoval, Rosa; Hennis, Anselm; Webb, Douglas; Tarlton, Dudley
Abstract : Economic analysis of interventions to reduce non-communicable diseases can encourage countries to increase investment, say Melanie Bertram and colleagues